PENGARUH HARGA, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI CAFÉ KUPI DATU BANJARBARU - Susiladewi Susiladewi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
This study aims to determine and analyze the effect of Price, Promotion and Quality ofservices provided by Café Kupi Datu on customer satisfaction both partially andsimultaneously. This research is quantitative research. The research design uses formal research procedures that contain clear definitions of research objectives and information needs. To answer and achieve the research objectives, regression analysis will be used. Regression analysis is a statistical method that aims to see the direction of the relationship and the magnitude of influence between 2 or more variables in a linear form. Therefore, the research model in this study is Y = α + βX + e. The results showed that, it turns out that the independent variable that has the largest beta is the Price variable (X1) that is equal to 0.659 or by 65.9%. Therefore it can be said that the variable that has the greatest effect on customer satisfaction Café Kupi Datu is the variable X1 (Price) with a standard regression coefficient of 0.659. The results of the first hypothesis (H1) are the decision to reject H0 and accept Ha, which means the F test of the regression equation obtained from this study shows the results that, together with the three variables price, promotion and quality of service affect the consumer satisfactionat Café Kupi Datu .